Developing a non-cadaveric brain tumour surgery lab in resource-constrained settings - Ahsan Ali Khan; Mohammad Hamza Bajwa; Fatima Gauhar; Saqib Kamran Bakhshi; Abdul Muqeet; Saleem Sayani; Izza Tahir; Faiza Urooj; Muhammad Usman Khalid; Syed Ather Enam (Journal of the Pakistan Medical Association, 2024)
Objective: To develop the country’s first brain tumour surgery lab in resource-constrained settings, for training young neurosurgeons and residents. Methods: A workshop was developed using mixed-fidelity models for assessing and training a participant’s psychomotor skills, hand-eye coordination, and teaching the principles of brain tumour surgery. Affordable noncadaveric models were used to compare and contrast the benefit of each teaching model. Within the existing space for wet labs at our institution, 8 different dissection stations were set up with adequate space for 2 people to work at a time. Each station was equipped with an operating room-Caliber microscope, a lighting system and a camera linked to a screen and high-powered electric drills and basic surgical equipment. Results: Our team was able to develop and use 3D-printed skull models and animal brain models for training in complex approaches and craniotomy. Conclusion: Surgical simulation training, in a cost-effective manner, provides the benefit of training residents and students in neurosurgical techniques in a safe, controlled environment leading to improvement in skills and technique. Keywords: Neurosurgery, surgical oncology, simulation training, Brain Neoplasms, Craniotomy, Skull